2011
DOI: 10.5194/acp-11-10727-2011
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of the stratospheric/tropospheric temperature trends in 1979–2008: multiple satellite MSU, radiosonde, and reanalysis datasets

Abstract: Abstract. The trends and spreads of tropospheric and stratospheric temperature are discussed in terms of three groups of datasets in 1979-2008. These datasets include (a) three satellite observations of Microwave Sounding Units (MSU) measurements, (b) five radiosonde observations and (c) five reanalysis products. The equivalent tropospheric and stratospheric temperature from radiosonde and reanalyses are calculated based on the vertical weighting function of the MSU channel 2 (CH2) and channel 4 (CH4) measurem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…To combine two such data sets, one of them needs to be converted to the vertical coordinate of the other, requiring knowledge of the vertical temperature profile, and also to a common concentration unit, requiring local temperatures. For long-term ozone trends, where changes are on the order of a few percent per decade, the uncertainties in long-term stratospheric temperature records can confound such conversions between vertical coordinate systems and concentration units (Davis and Rosenlof, 2012;Thompson et al, 2012;Wang et al, 2011;McLinden and Fioletov, 2011;Xu and Powell, 2011). Any artificial trend in stratospheric temperature structure, which affects the altitudes of pressure levels, can alias into ozone trends (WMO, 2015;McLinden and Fioletov, 2011;Rosenfield et al, 2005).…”
Section: Issues Related To Merging Data From Several Recordsmentioning
confidence: 99%
“…To combine two such data sets, one of them needs to be converted to the vertical coordinate of the other, requiring knowledge of the vertical temperature profile, and also to a common concentration unit, requiring local temperatures. For long-term ozone trends, where changes are on the order of a few percent per decade, the uncertainties in long-term stratospheric temperature records can confound such conversions between vertical coordinate systems and concentration units (Davis and Rosenlof, 2012;Thompson et al, 2012;Wang et al, 2011;McLinden and Fioletov, 2011;Xu and Powell, 2011). Any artificial trend in stratospheric temperature structure, which affects the altitudes of pressure levels, can alias into ozone trends (WMO, 2015;McLinden and Fioletov, 2011;Rosenfield et al, 2005).…”
Section: Issues Related To Merging Data From Several Recordsmentioning
confidence: 99%
“…These time-varying errors can introduce spurious trends without being eliminated by data assimilation systems. Many spurious variations in climate signals were also identified in the early-generation reanalyses (Bengtsson et al, 2004;Andersson et al, 2005;Chen et al, 2008;Wang, 2016a, 2017a;Schoeberl et al, 2012;Xu and Powell, 2011;Hines et al, 2000;Cornes and Jones, 2013). Therefore, reanalyses produced using the existing reanalysis strategy may not accurately capture climate trends (Trenberth et al, 2008), even though they may contain relatively accurate estimates of synoptic or interannual variations in the Earth's atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…R s values based on the revised Ångström-Prescott equation (Wang et al, 2015;Yang et al, 2006;Wang, 2014) are used in this study. The derived R s values consider the effects of Rayleigh scattering, water vapour absorption, and ozone absorption (Wang et al, 2015;Yang et al, 2006) and can accurately reflect the effects of aerosols and clouds on R s over China Tang et al, 2011). Several intensive studies have reported that the derived R s values can accurately depict the interannual, decadal and long-term variations in R s (Wang et al, , 2015Wang, 2014).…”
Section: Observational Datasetsmentioning
confidence: 99%